The fundamental rights challenges of algorithms. Issue 3 (September 2019) - Gerards, Janneke
Algorithms form an increasingly important part of our daily lives, even if we are often unaware of it. They are enormously useful in many different ways. They facilitate the sharing economy, help detect diseases, assist government agencies in crime control, and help us choose what series or film to watch. Yet, there is also a darker side to algorithms, and that is that they (and their applications) can easily interfere with our fundamental rights. This column explores some of the main fundamental rights challenges set by the pervasiveness of algorithms, and it presents a brief outlook for the future.